'Akerman' on-screen: Chantal Akerman behind and before the camera, and after cinema. (1st September 2019) - Pollock, Griselda
To challenge the increasing tendency to read Chantal Akerman's oeuvre autobiographically, this article analyses two documentaries on the filmmaker. It theorizes the effects of the increasingly frequent appearance of the filmmaker on screen in such documentaries and in her own films by reviewing both tendencies through the classic debates about authorship. Noting and critiquing the way in which the documentary filmmakers attempt to mimic 'Akerman' filmmaking, the article argues that their attempts betray the codes that constitute 'Akerman' cinema by reproducing the modes against which her cinema worked. 'Akerman' names a cinematic journey towards the formulation of an aesthetic language of space, shot, frame and temporality through which to make visible the unseen and make audible the unspoken that constituted both the conditions and the imperative for a cinematic intervention from a historically situated post-war, post-Shoah 'Polish Jewish family in Brussels'. This article proposes the term filmworking (drawing on Bracha Ettinger's post-traumatic concept of artworking) to reveal how Akerman queered cinema. This effect emerges only from close analysis of each instance of filmworking and not from the closed tropes of a retrospective narrative of the life of the filmmaker, who, being repeatedly interviewed, herself contributed to such extra-cinematic explanations and closures of her own work.